2023
DOI: 10.5851/kosfa.2022.e60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Novel High-Intensity Ultrasound Technique on Physio-Chemical, Sensory Attributes, and Microstructure of Bovine Semitendinosus Muscle

Abstract: Ethics approval (IRB/IACUC) (This field may be published.) This article does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Significantly high correlations between WBSF and sensory tenderness scores have been obtained by a number of authors (Lee et al, 2022; Silva et al, 2017). Results of physical and palatability attributes for LTL muscles based on pH are given in Table 2.…”
Section: Resultsmentioning
confidence: 89%
“…Significantly high correlations between WBSF and sensory tenderness scores have been obtained by a number of authors (Lee et al, 2022; Silva et al, 2017). Results of physical and palatability attributes for LTL muscles based on pH are given in Table 2.…”
Section: Resultsmentioning
confidence: 89%
“…Tenderness is the most important attribute influencing beef palatability [ 25 , 26 ] while WHC is the most important attribute for the sensory properties of pork [ 1 , 27 ]. Therefore, in this respect, improvements in tenderness and WHC have been extensively studied in beef and pork, respectively, in relation to the development of aging techniques [ 11 , 21 ].…”
Section: Mechanism Of Postmortem Aging On Changes In Meat Qualitymentioning
confidence: 99%
“…WHC is one of the most important quality traits of fresh meat because it is closely related to meat color, texture, and tenderness [ 1 , 11 ]. An increase in water loss is unavoidable due to the occurrence of rigor mortis in the process of conversion from muscle to meat.…”
Section: Mechanism Of Postmortem Aging On Changes In Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Amiri et al [18] indicated that HIU treatment (100 and 300 W for 30 min) reduced the particle size of bovine-derived MPs and improved their rheological and functional properties. Lee et al [19] reported that HIU treatment (35 kHz, 800 W, 60 min) could improve sensory characteristics through tenderizing without impairing the quality of the bovine semitendinosus muscle. Studies have reported the physicochemical properties of MPs after US treatment, but not many have identified the cause or confirmed its potential as an O/W emulsion stabilizer.…”
Section: Introductionmentioning
confidence: 99%